Soil Physics Analysis of pH and Water Retention Capacity in Productive Paddy Fields and Soils Degraded by Waste-Burning Residues - Khairiah, Khairiah; Siregar, Hanna Aulia; Agustini, Insya Widiya; Kechik, MM Awang (Universitas Islam Negeri Ar-Raniry, 2026)
This study investigated the differences in soil pH and water retention capacity between productive paddy soil and soil degraded by waste combustion residues from a soil physics perspective. The waste combustion soil used was household waste combustion soil containing organic and inorganic waste. Combustion residues can alter the physicochemical properties of the soil, particularly porosity, capillarity, and moisture dynamics, which affect soil water retention behavior. A comparative quantitative approach was used by collecting soil samples at a depth of 0–20 cm from two different locations. Soil pH was measured using a digital pH meter, while water retention capacity was analyzed using standard laboratory procedures. The results showed that the productive paddy soil exhibited a pH close to neutral (6.8), higher porosity, stronger capillary action, and high water retention capacity (90%). In contrast, the degraded soil exhibited alkaline conditions (pH 8.7), reduced pore connectivity, impaired moisture dynamics, and lower water retention capacity (60%). These findings suggest that waste combustion residues negatively impact soil structure and water retention mechanisms. Therefore, appropriate waste management and soil rehabilitation strategies are needed to restore soil function and agricultural productivity.